Benefits of a European Project on Diagnostics of Highly Pathogenic Agents and Assessment of Potential “Dual Use” Issues - Grunow, Roland; Ippolito, G.; Jacob, D.; Sauer, U.; Rohleder, A.; Di Caro, A.; Iacovino, R. (Frontiers in Public Health, 2014)
R. Grunow1 (Coordinator), G. Ippolito2 (Co-Coordinator), D. Jacob1, U. Sauer1, A. Rohleder1, A. Di Caro2, R. Iacovino2, and on behalf of the QUANDHIP partners3 1-Robert Koch Institute, Berlin, Germany; 2- L. Spallanzani National Institute for Infectious Diseases, Rome, Italy; 3- http://www.quandhip.info/Quandhip/EN/Home/Homepage_node.html QUANDHIP (Quality Assurance Exercises and Networking on the Detection of Highly Infectious Pathogens) is a Joint Action initiative set up in 2011 that has successfully unified the primary objectives of the European Networks on Highly Pathogenic Bacteria (ENHPB) and of P4 laboratories (ENP4) both of which aimed to improve the efficiency, effectiveness and response capabilities of laboratories directed at protecting the health of European citizens against high consequence bacteria and viruses of significant public health concern. Both networks have established a common collaborative consortium of 37 nationally and internationally recognized institutions with laboratory facilities from 22 European countries. The specific objectives and achievements include the initiation and establishment of - a recognized and acceptable quality assurance scheme, including practical External Quality Assurance Exercises, comprising living agents, that aim to improve laboratory performance, accuracy and detection capabilities in support of patient management and public health responses. - recognized training schemes for diagnostics and handling of highly pathogenic agents - an international repository comprising highly pathogenic bacteria and viruses for the development of standardized reference material - a standardized and transparent biosafety and biosecurity strategy safeguarding healthcare personnel and the community in dealing with high consequence pathogens - the design and organisation of response capabilities dealing with cross border events with highly infectious pathogens including the consideration of diagnostic capabilities of European in